تحليل أثر الانفاق العام على النمو الاقتصادي في ليبيا: دراسة قياسية تطبيقية، خلال الفترة (2014-1970) - Abdel Moneim Amraaj Adam; Mohamad Sabri Harun; Abdullah MohammedAyedh (Design for Scientific Renaissance, 2024)
Volume: 8 No: 8